Basics of Greek accents: eight lessons with exercises - Lee, John A. L. (HarperCollins Christian Publishing, 2018)
Basics of Greek Accents by John A. L. Lee is a compact, student-friendly, and practical guide intended to introduce students to the basics of ancient Greek accents, whether classical or biblical, giving them a foundation they will use as they continue their studies.